Molecular evolution of the alpha-amylase genes of Bombyx mori and other insects. - Simons, Pamela J. (University of Ottawa (Canada), 1993)
The gene of the ubiquitous starch degrading enzyme $\alpha$-amylase has been chosen to study evolutionary mechanisms and the relationships between several insect groups. In this project, the $\alpha$-amylase gene sequence of a representative of the order Lepidoptera, Bombyx mori, was determined. The coding region of Bombyx and the seven other insect genes are approximately the same size and have at least 60% identity with one another. There are various numbers of introns dispersed throughout the loci but often sites are shared between two or more species. There is evidence of differing codon biases among the genes with Drosophila and Anopheles being very GC rich and Choristoneura and Tribolium having virtually no bias. Biases caused discrepancies between the phylogenetic trees created by several different methods. Representatives of the same order always grouped together as predicted, but the order within the Lepidoptera varied with the method used. (Abstract shortened by UMI.)
Keywords: Biology, Molecular.